ANALISIS PROFIL LITERASI SAINS PESERTA DIDIK SMP DI SIDOARJO BERDASARKAN INDIKATOR PISA 2025 - Wardani, Zabrina Aulia; Hidayati, Siti Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the scientific literacy profile of junior high school students in Sidoarjo based on PISA 2025 indicators. Scientific literacy is an essential competency for understanding and applying science in daily life, yet students’ literacy levels in Indonesia remain low. This research used a quantitative descriptive survey design. The instrument was adapted from the PISA 2025 framework, consisting of 9 multiple-choice questions covering three indicators: explaining phenomena scientifically, evaluating and designing scientific inquiry, and interpreting data for decision-making. The sample involved 30 seventh-grade students at SMPN 2 Krian, Sidoarjo. Data were analyzed using percentage calculations and categorized into criteria levels. The results showed that overall scientific literacy was in the low category (50%). The highest score was on explaining scientific phenomena (69%, high), while the lowest was on using scientific information for decision-making (39%, very low). These findings indicate the need for innovative, contextual, and student-centered learning strategies.